FEATURES OF SPEECH DEVELOPMENT IN CHILDREN WITH MENTAL RETARDATION - Shermatova Yoqutkhan (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes the concept of retarded mental development, the specific characteristics of the speech characteristics of children with retarded mental development, the development of vocabulary, the variety of speech defects and psychopathological features of this type of children, and the researches by scientists.